Strategies that Improve the Language Learning Experience of Seventh Graders with Deficit and Lack of Attention in the English Class (2018)
ABSTRACT: This action research project reports the implementation of strategies that increase the motivation and the level of attention of a group of students who present difficulties to stay attentive in the English class; including students with an ADHD diagnosis. This project was carried out with seventh graders of the Gimnasio Cantabria School. The data was collected through class observations, voice recordings, analysis of students¿ log and surveys. The results show that the students increased their attentiveness, motivation and performance in at least one of the language skills.